PENGARUH DIVIDEN PAYOUT RATIO, TINGKAT PERTUMBUHAN, DAN UKURAN PERUSAHAN TERHADAP STRUKTUR MODAL PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA PERIODE 2013-2017. - David David; Basuki Toto Rahmanto (LPMP Imperium, 2020)
Abstract: This study aims to determine the effect of dividend payout ratio, firm size, and company growth rate on the capital structure of pharmaceutical companies in Indonesia Stock Exchange year 2013-2017. The sample selection technique used purposive sampling and research sample obtained 9 companies. The data analysis method used is multiple linear regression analysis. Data analysis techniques used are classical assumption test and multiple linear analysis. Based on the results of the analysis shows that the dividend payout ratio does not affect the capital structure, firm size does not affect the capital structure, corporate growth has no effect on capital structure.